Comparación del esmalte dental de los molariformes en las liebres mexicanas - Romero-Palacios, Adriana; Cervantes, Fernando (THERYA, 2012)
At this time there is no hypothesis of kinship in Mexican hares based on a comparison of the molariform tooth enamel, which represent valuable of information for systematic purposes, used to describe fossil and extant species. We describe the patterns of the enamel of five species of hares using the second and third upper premolars and third lower premolar. The enamel pattern was identified and described using a microscope and reference photographs. The enamel pattern was compared among species and informative characters were identified or recognized, in order to discriminate species. We also found that the third lower upper molar and the second upper premolar were the most useful teeth to better discriminate the species. It was found that L. insularis is closer to L. californicus, they share a simple enamel pattern, while L. alleni shows a complex pattern in number of folds and forms, and is more similar to L. callotis and L. flavigularis. It was concluded that these characters distinguish the pattern of tooth enamel, which generally shows little variation within the species, but more significantly among species.